Highly soluble 3,4-(dimethoxyphenylthio) substituted phthalocyanines: Synthesis, photophysical and photochemical studies - Ozturk, Cansu; Erdogmus, Ali; Durmuş, Mahmut; Ugur, Ahmet Lutfi; Kilicarslan, Fatma Aytan; Erden, Ibrahim (Pergamon-Elsevier Science Ltd, 2012)
The synthesis of a new 3,4-(dimethoxyphenylthio) substituted phthalonitrile (1) and its soluble metal free (2), zinc (II) (3), oxo-titanium (IV) (4) and nickel (II) (5) phthalocyanine derivatives are reported for the first time. The new compounds have been characterized by elemental analysis, FT-IR, H-1 NMR, UV-Vis, fluorescence spectroscopies and mass spectra. General trends are described for fluorescence, photodegradation and singlet oxygen quantum yields and fluorescence lifetimes of oxo-titanium (IV) and zinc (II) phthalocyanine compounds in dimethylsulfoxide (DMSO). The effects of the metal ion on the photophysical and photochemical parameters for these phthalocyanines (3 and 4) are also reported. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Zinc; Nickel; Titanium; Fluorescence; Photochemistry; Photophysics